1999
DOI: 10.1021/a1990008k
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals and Related Drugs

Abstract: It does not cover biochemical or clinical aspects but deals only with unformulated and formulated products. The review continues to be divided into 11 major sections and in some cases subsection either by subtopic or by technique. Because of space limitations, a citation generally appears only in a single section and the articles selected do not represent an exhaustive review of the topics. GENERAL INFORMATIONExamples of comprehensive books and reviews that have been published in the last two years include the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 300 publications
0
17
0
Order By: Relevance
“…Their mode of interaction is as potent prostaglandin synthetase inhibitors [1][2][3][4][5]. Since their introduction many manuscripts have appeared that discuss various structural and physical properties of fenamates [6][7][8][9][10][11][12] as well as numerous individual analytical methods for quantifying them [1][2][3][4][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Their mode of interaction is as potent prostaglandin synthetase inhibitors [1][2][3][4][5]. Since their introduction many manuscripts have appeared that discuss various structural and physical properties of fenamates [6][7][8][9][10][11][12] as well as numerous individual analytical methods for quantifying them [1][2][3][4][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…1 Several methods have been applied to detect phenothiazine derivatives, such as spectrophotometry, 2 colorimetry, 3 liquid chromatography (LC) 4 and titrimetry. 5 Promethazine hydrochloride, a prominent compound in the large group of phenothiazine derivatives, is widely used as a therapeutic agent for treating various mental and personality disorder. Daniela et al 6 have reported the determination of promethazine hydrochloride in a pharmaceutical preparation using a flow-injection spectroelectroanalytical method.…”
mentioning
confidence: 99%
“…1 This agent is commonly given for the prophylaxis and control of hemorrhages from small blood vessels in surgery and clinical conditions. [2][3][4] Although this compound has been extensively applied for clinical purposes, only a few methods have been reported for the quantitative determination of ethamsylate in pharmaceutical and biological fluids; these include spectrophotometry, 1 electrochemistry, [5][6][7] chemiluminescence, 8 and HPLC method. 9 Equivalence assessment will demonstrate that results obtained will not differ importantly when different methods are used for the same intent.…”
Section: Introductionmentioning
confidence: 99%